2019
DOI: 10.3390/en12132592
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Energy Consumption and Energy-Saving in High-Quality Olive Oil Decanter Centrifuge: Numerical Study and Experimental Validation

Abstract: In this study, an energy consumption model of a decanter centrifuge was proposed, in particular for a technologically evolved machine equipped with an electromechanical recovery system. This model should be suitably coupled with an auto-adaptive controlling technique used to accurately manage the olive oil process. To achieve this goal, a solid physical and theoretical basis that simple to implement is required. To date there have only been limited scientific studies modelling energy consumption applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In particular, the studied biomass is not a homogeneous mixture due to the seasonality of the production and the presence of a solid phase (pulp and pitted pomace) and a liquid phase (vegetation water). These two components have a different composition that is variable over time [1][2][3][4], so they should be stored in separate tanks and properly mixed both during storage and before being sent to the digester.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the studied biomass is not a homogeneous mixture due to the seasonality of the production and the presence of a solid phase (pulp and pitted pomace) and a liquid phase (vegetation water). These two components have a different composition that is variable over time [1][2][3][4], so they should be stored in separate tanks and properly mixed both during storage and before being sent to the digester.…”
Section: Resultsmentioning
confidence: 99%
“…This increase may also be due to the addition of urea which, in this specific case, could be further reduced. In fact, in these tests the inlet carbon/nitrogen ratio (Table 2) in the biomass is balanced but the excess of carbon compared to nitrogen is easily verifiable in the olive oil wastewater, especially as regards the pomace [1]. The rebalancing of the C/N ratio would produce better effects if waste materials with high protein content are used instead of urea, i.e., vegetable waste from legumes, slaughter by-products, pooled feces, etc.…”
Section: Plant Performancementioning
confidence: 99%
See 1 more Smart Citation
“…So, energy can be considered like a raw material to come up with quality products at affordable costs [3,4]. Energy consumption and energy efficiency potential can be evaluated using both mathematical modelling and/or experimental validation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in the literature research can be found regarding energetic [1,16,27,28], economic [29,30] and exergetic [31,32] aspects concerning CHP plants, but only a few authors provide a complete analysis of these three aspects as a whole for the food industry [33]. Studies are frequently carried out separately from many CHP applications, which however provide important indicators that can be used as useful support for the optimum selection and sizing of a cogeneration plant as applied to the food industry [34,35].…”
Section: Introductionmentioning
confidence: 99%